Los extranjeros y su participación en el primer período de la Independencia en la Nueva Granada, 1808-1816 (2010)
ABSTRACT: The independence movements of the First Republic in New Granada (1810-1815) included foreigner citizens, hired to train cadets, to organize military academies and battalions, or to serve as officers. There was an important group formed by French people, characterized by fleeting success, its rivalry with Simón Bolívar, and whose members died in battle or escaped when Pablo Morillo armies arrived.